ТЕОРИЯ ФОРМИРОВАНИЯ И РАЗВИТИЯ БИОЛОГИЧЕСКИХ ПОНЯТИЙ - Шарибаева, У.О.; Турекеева, А.Ж. (SCIENCE and SOCIETY, 2025)
This article examines the continuous and enduring relationships between individuals and society in the formation of biological concepts among students. It explores the dissemination of scientific and humanistic perspectives, investigates issues in the development of biological concepts, and discusses the practical application of theoretical knowledge. Additionally, the article considers the potential for enhancing students’ cognitive abilities in the realm of biological concepts and methods for developing their critical thinking skills.